2002
DOI: 10.1016/s0927-6505(01)00112-8
|View full text |Cite
|
Sign up to set email alerts
|

Design study of CANGAROO-III, stereoscopic imaging atmospheric Cherenkov telescopes for sub-TeV γ-ray detection

Abstract: CANGAROO-III is an Imaging Atmospheric Cherenkov Telescope (IACT) array of four 10 m telescopes for very high energy (sub-TeV) gamma-ray astronomy. A design study of Preprint submitted to Elsevier Preprint 24 October 2018 the CANGAROO-III telescope system was carried out using the Monte Carlo technique in order to optimize the pixel size and the telescope spacing. Studies were also made of observations at low elevation angles.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2002
2002
2009
2009

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(30 citation statements)
references
References 11 publications
(11 reference statements)
0
30
0
Order By: Relevance
“…Indeed, there are already such arrays of telescopes planned or in operation such as CANGAROO [21], HESS [22], VERITAS [23] and MAGIC [24]. In particular, CANGAROO and HESS are well located to observe the galactic center for a sizable fraction of their observing time.…”
Section: The Detectability Of Nr Through Gamma-raysmentioning
confidence: 99%
“…Indeed, there are already such arrays of telescopes planned or in operation such as CANGAROO [21], HESS [22], VERITAS [23] and MAGIC [24]. In particular, CANGAROO and HESS are well located to observe the galactic center for a sizable fraction of their observing time.…”
Section: The Detectability Of Nr Through Gamma-raysmentioning
confidence: 99%
“…The time structure of the image can be used in the data analysis as an additional parameter as it is shown in [7]. Recent experiments with large reflectors like CANGAROO [8,9], HESS [10,11], MAGIC [12,13], VERITAS [14,15] made a major contribution to the very fast development of ground-based γ-ray astronomy (see figure 1 in [16]). The detection of low energy events is possible by using a very large telescope, which requires a parabolic shape of the main reflector dish (like that in MAGIC) to avoid broadening of the time profile of the Cherenkov signal.…”
Section: Introductionmentioning
confidence: 99%
“…The number of excess events was determined from the plots of image orientation angle a for on-and off-source runs (inset) to be 3,417±240 (14.3σ). The γ-ray acceptance efficiency was calculated using the Monte Carlo method 26 . In order to check our simulations, we analysed Crab nebula data obtained in December 1999 and December 2000, and found that the flux was consistent with previous experiments 28 to within 12%.…”
mentioning
confidence: 99%